Experimental study of the 2D variability roughness in the honing process of the steel cylinder (2018)
This article presents the study of the surface roughness inside cylinders, machined by honing in industrial honing machines, with a detailed review of the variability of the values obtained in the measurement of the machined surface. The determination of the amount of measurement data on the cover is displayed to get characteristic mean values of the measured surface. For this reason, and due to the randomness of the surfaces machined by honing, an experimental study has been proposed to carry out this analysis, where the roughness has been measured with a roughness meter with a contact probe, since this type of instrument is widely used academically and especially industrially, and is apparently standardized by international standards such as ISO 3274 or ASME B46.1.